Impact of Operating Costs and Sales Revenue on Net Profit IDX Garment and Textile Sector - Ramdan, Mohamad Fatur; Al Fikri, Muhammad Haykal; Raffif Fabiano, Gerrard; Zahra, Astri; An Khofiyah, Nida (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
This study aims to examine the effect of operating costs and sales revenue on net profit in garment and textile sector companies listed on the Indonesia Stock Exchange (IDX) during the 2023–2024 period. A quantitative approach was used with a multiple linear regression method, utilizing data collected from the annual financial reports of 20 companies selected through purposive sampling. Data analysis was conducted using descriptive statistics, classical assumption tests, multiple regression tests, t-tests, F-tests, and the coefficient of determination (R²) assisted by SPSS 26 software. The results indicate that both operating costs and sales revenue, either partially or simultaneously, do not have a significant effect on net profit. The R Square value of 28.3% suggests that other factors outside the research model predominantly influence the companies' net profits. These findings highlight the importance for management to be more adaptive to external dynamics such as raw material price fluctuations and global competition, and to emphasize market diversification and product innovation to improve future financial performance.